Groundwater development in eastern India: Overview - Meinzen-Dick, Ruth S. (International Food Policy Research Institute, 1990)
The chapters presented in this section identify needs and potential for groundwater development and conjunctive use, with special reference to eastern India. The first chapter by T. Prasad and I. D. Sharma, and the second chapter by Niranjan Pant, both make the case that the eastern region lags behind the rest of India in agricultural production and many other economic indicators despite its plentiful groundwater and other natural resources, which provide the potential for development. These two papers identify technical and socioeconomic issues related to increasing groundwater use in a context of large numbers of small and resource-poor farmers. The third chapter, by Tushaar Shah, draws on an empirical example from Gujarat in western India to present a strategy for developing conjunctive use of groundwater in the command of surface irrigation systems.